The impact of transformational leadership on employee performance and organizational commitment - Gevorgyan, Veronika (2024)
This dissertation investigates the role of transformational leadership in influencing key employee outcomes, such as affective organizational commitment, job performance, employee engagement, and job satisfaction. In a rapidly changing organizational environment, understanding the impact of leadership styles is essential for fostering a committed and high-performing workforce. Transformational leadership, known for its emphasis on inspiration, motivation, and individual consideration, provides a framework for driving positive organizational outcomes. The research employed a quantitative approach, using an online survey to collect data from employees across various industries. A total of 180 responses were analyzed using SmartPLS to estimate a Partial Least Squares Structural Equation Model (PLS-SEM). This method enabled the study to assess the relationships between transformational leadership and employee outcomes, testing the proposed hypotheses. The findings confirmed that transformational leadership significantly enhances affective organizational commitment and employee engagement, positively influencing job performance and job satisfaction. This study contributes to academic literature and managerial practice by providing empirical insights into how transformational leadership can shape a supportive and productive work environment. The results emphasize the importance of leadership development programs that cultivate transformational behaviors to enhance employee well-being and organizational success.